2021
DOI: 10.1002/ccr3.5054
|View full text |Cite
|
Sign up to set email alerts
|

Primitive pelvic bone hydatidosis: What an amazing extension

Abstract: Hydatidosis is an anthropozoonosis caused by the larval stage of Echinococcus tapeworms. 1 It is a worldwide infectious disease but highly endemic in North Africa, the Middle East, and South America. 2 It could be caused by different species, but Echinococcus granulosus species is responsible for more than 95% of human hydatid disease. 3 The latter is mainly encountered in pastoral areas where the contact between dogs and sheep is frequent. The prevalence of this disease is most likely underestimated due to it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Iliac bone involvement has a poor functional prognosis due to extension to the hip joint and more rarely to the sacrum [10]. Bone hydatid cyst has been called "white cancer" [15]. The surgery is often debilitating, with a high risk of recurrence [16].…”
Section: Prognosismentioning
confidence: 99%
“…Iliac bone involvement has a poor functional prognosis due to extension to the hip joint and more rarely to the sacrum [10]. Bone hydatid cyst has been called "white cancer" [15]. The surgery is often debilitating, with a high risk of recurrence [16].…”
Section: Prognosismentioning
confidence: 99%
“…The most common location for BH is the vertebrae, accounting for approximately 50% of cases, followed by the pelvis and long bones of the lower limb. Previous reports have considered the pelvis as the second most common location for BH, with an occurrence rate of approximately 28% [ 5 ]. The ilium is the preferred site for pelvic hydatidosis, as previously noted by Zlitni et al The same study reported an infection rate of 30%, which is a crucial factor in the treatment protocol and patient prognosis [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…mostly with E. granulosus (cystic echinococcosis; CE) and/or E. multilocularis (alveolar echinococcosis; AE). The disease is transmitted between humans and animals and seriously threatens human health [ 1 , 2 ]. The incidence of echinococcosis is low, but biological behavior of the parasites is quite complex.…”
Section: Introductionmentioning
confidence: 99%